Soil carbon sequestration and land use change associated with biofuel production: empirical evidence. Issue 1 (12th March 2015) - Qin, Zhangcai; Dunn, Jennifer B.; Kwon, Hoyoung; Mueller, Steffen; Wander, Michelle M.
Abstract: Soil organic carbon (SOC) change can be a major impact of land use change (LUC) associated with biofuel feedstock production. By collecting and analyzing data from worldwide field observations of major LUCs from cropland, grassland, and forest to lands producing biofuel crops (i.e. corn, switchgrass, Miscanthus, poplar, and willow), we were able to estimate SOC response ratios and sequestration rates and evaluate the effects of soil depth and time scale on SOC change. Both the amount and rate of SOC change were highly dependent on the specific land transition. Irrespective of soil depth or time horizon, cropland conversions resulted in an overall SOC gain of 6–14% relative to initial SOC level, while conversion from grassland or forest to corn (without residue removal) or poplar caused significant carbon loss (9–35%). No significant SOC changes were observed in land converted from grasslands or forests to switchgrass, Miscanthus, or willow. The SOC response ratios were similar in both 0–30 and 0–100 cm soil depths in most cases, suggesting SOC changes in deep soil and that use of top soil only for SOC accounting in biofuel life cycle analysis (LCA) might underestimate total SOC changes. Soil carbon sequestration rates varied greatly among studies and land transition types. Generally, the rates of SOC change tended to be the greatest during the 10 years following land conversion and had declined to approach 0 within about 20 years for most LUCs. Observed trends in SOC change were generally consistent with previous reports. Soil depth and duration of study significantly influence SOC change rates and so should be considered in carbon emission accounting in biofuel LCA. High uncertainty remains for many perennial systems and forest transitions, additional field trials, and modeling efforts are needed to draw conclusions about the site‐ and system‐specific rates and direction of change.